ANALISA METODE WEIGHTED SUM MODEL (WSM) PENERIMA KARTU INDONESIA PINTAR (KIP) KEPADA SISWA/I DI SD (SEKOLAH DASAR) - Marlina Drawati Saragih; Heru Satria Tambunan; Rafiqa Dewi (STMIK Budi Darma, 2019)
Indonesia Smart Card is a cash assistance from the government given to students whose parents are less able to finance their education. As a continuation and expansion of the objectives of the Poor Student Assistance (BSM) program. KIP has the goal of increasing access for children aged 6 (six) to 21 (twenty one years). In Primary School 091329 in the recipient of the Smart Indonesia Card faces many problems As students who are entitled to receive assistance actually do not receive. because of that there were protests and demonstrations caused by Kartu Indonesia Pintar which were not on target. The criteria for Indonesian card recipients are smart social protection card holders, parents' income, no vehicles, no dependents, orphans. In its implementation, it certainly has obstacles in deciding who students get the smart Indonesian card. To solve the problem, a weighted Sum Model (WSM) decision support system can overcome this problem. By applying the Weighted Sum Model (WSM) which is relatively easy and fast, it is believed to be able to get the best results. This research can provide information to the school in the recipient of the Indonesia Smart Card (KIP) for the following year. Keywords: SPK, Weighted Sum Model (WSM), Receiver of Smart Indonesia Cards